(untitled) (Clío & Asociados. La historia enseñada, 2024)
In this paper we propose to review some of the national commemorations thatbelong to the nineteenth century. Based on the experience of teaching a degree subject in the History Professorate of the Universidad Nacional de Mar del Plata, we intend to analyse the link between the historical account and the school act. We believe that the event can be resignified as a moment of visibility of relegated actors, phenomena and concepts. Based on this assumption, we aim to analyze three key aspects that are developed in the sections of this paper. First, we examine how certain ephemeris are established and the role of historians in this process. Then, we critically evaluate both the anniversaries and the educational purpose of the teaching of history in secondary education. Finally, through concrete cases, we observe how the commemorations of these dates can offer new perspectives and meanings.